Tracing the Impact of COVID-19 on Early Language and Literacy Development from Pre-K Through First Grade - Elizabeth Burke Hadley; Siyu Liu; Eunsook Kim; Meaghan McKenna; Katharine Hull (AERA Open)
COVID-19 disrupted early educational experiences for a generation of children, but research on how missing school impacted academic development for young children is limited. This paper investigated the longitudinal impact of COVID-19 on the language and literacy development of children in a Florida school district, specifically following children who were in pre-K in March 2020 through the end of first grade. This COVID-19 cohort (n = 1,167) was compared with a pre-COVID-19 cohort (n = 1,211) using propensity score matching, multilevel regression models, and linear growth modeling. Results indicated that the negative impacts of COVID-19 on language and literacy emerged late and increased over time for young children but were not driven primarily by remote learning. Young children showed especially severe learning loss in unconstrained literacy skills (e.g., comprehension) versus constrained skills (e.g., phonics). COVID-19 impacts were not moderated by child characteristics (e.g., poverty or race/ethnicity).